An evaluation of the production effects of video self-modeling. (December 2017) - O'Handley, Roderick D.; Allen, Keith D.
Highlights: An adult male with Intellectual Disability and Autism Spectrum Disorder was included. Intervention was conducted in the participant's home. Video self-models for three activities of daily living tasks were produced. Producing video-self models, but not viewing them, increased task accuracy. Viewing video self-models resulted in little additive benefit in task accuracy. Abstract: A multiple baseline across tasks design was used to evaluate the production effects of video self-modeling on three activities of daily living tasks of an adult male with Autism Spectrum Disorder and Intellectual Disability. Results indicated large increases in task accuracy after the production of a self-modeling video for each task, but before the video was viewed by the participant. Results also indicated small increases when the participant was directed to view the same video self-models before being prompted to complete each task.